2016
DOI: 10.1111/jdi.12472
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy is associated with diabetes: Evidence from meta‐analysis

Abstract: Aims/IntroductionThere is still no obvious evidence proving that androgen deprivation therapy (ADT) would increase the risk of diabetes. To determine if ADT is associated with diabetes in men with prostate cancer, we carried out the present study.Materials and MethodsWe systematically searched Medline, Embase and the Cochrane Library Central Register through 2014. Studies comparing ADT vs control aimed at treating prostate cancer reporting diabetes as outcome were included. Data were extracted independently by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…However, other SRMA studies found 10-38% and 17% increases in the incidence of CV disease and CV death, respectively [64,65], and a 12% increase in the risk for stroke [66]. SRMAs have also found that androgen deprivation therapy altered body composition by increasing body fat and decreasing lean body mass [67], increased the risk of diabetes by 36-39% [68,69], and increased the risk for MetS by 75% [69]. These results provide a consensus that androgen deprivation increases the risk of T2DM, MetS, and CV disease.…”
Section: Effects Of Androgen Deprivation Therapy For Prostate Cancer mentioning
confidence: 99%
“…However, other SRMA studies found 10-38% and 17% increases in the incidence of CV disease and CV death, respectively [64,65], and a 12% increase in the risk for stroke [66]. SRMAs have also found that androgen deprivation therapy altered body composition by increasing body fat and decreasing lean body mass [67], increased the risk of diabetes by 36-39% [68,69], and increased the risk for MetS by 75% [69]. These results provide a consensus that androgen deprivation increases the risk of T2DM, MetS, and CV disease.…”
Section: Effects Of Androgen Deprivation Therapy For Prostate Cancer mentioning
confidence: 99%
“…for meta-analysis from four cohort and four cross sectional studies. Incidence of diabetes amongst men receiving ADT (GnRH agonists, combined androgen blockade or orchiectomy) was 10.9% (27). The risk of diabetes was 39% higher for these men than for men not receiving ADT or men on watchful waiting or active surveillance (RR 1.39; 95%CI 1.27-1.53, P<0.001) (27).…”
Section: C Fracturementioning
confidence: 99%
“…Incidence of diabetes amongst men receiving ADT (GnRH agonists, combined androgen blockade or orchiectomy) was 10.9% (27). The risk of diabetes was 39% higher for these men than for men not receiving ADT or men on watchful waiting or active surveillance (RR 1.39; 95%CI 1.27-1.53, P<0.001) (27). Sub group analyses for ADT type and duration showed that GnRHa, combined androgen blockade and orchiectomy are significantly associated with risk of diabetes, and longer duration of ADT with elevated risk (27).…”
Section: C Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…ADT has been linked to decreased insulin sensitivity, 43 diabetes 44,45 and alterations in body composition. In fact, in 2010, the FDA issued a safety warning on the labels of GnRH agonists regarding an increased risk of diabetes (due to the development of insulin resistance or altered insulin sensitivity), obesity and other metabolic changes.…”
Section: Safetymentioning
confidence: 99%